GOALS AND MAIN GUIDELINES OF ENERGY SECURITY IN THE CONDITIONS OF THE WAR-TIME ECONOMY - NOVOSAD, OKSANA; MATIICHUK, LIUBOMYR; PAVLOVA, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Ukraine’s energy potential during wartime has been clarified. The work of scientists, researchers, and practitioners on the goals and strategies of energy system development is analyzed. The main stages of the formation of energy security as a socio-economic category during the transformation changes are outlined. The most important of them is the stage of long-term policy and centralized management; the stage of active transformational shifts of the economy in the 1990s, systemic crisis phenomena, processes of decentralization of the management system; stage of stability and reproduction in the innovative provision of energy regulation of the fuel and energy sector; the stage of the revival of energy security in the postwar period (started in March 2022 - continues to this day). The role and significance of such processes as globalization, liberalization, and diversification, which impact expanding the boundaries of the integration energy environment, have been studied. The objectivity in achieving energy security is generalized; the following directions are singled out: - traditional types of energy (coal, gas, oil products); hydropower; nuclear energy; renewable energy sources. Economic categories are structured according to the impact on energy security at the micro, macro, and mezo levels. The goals and main strategies of ensuring the EB during the martial law economy of Ukraine are systematized. Suggestions for the optimal and most economically sound way to achieve them are given. The complementary nature of implementing an energy security strategy is possible by identifying and avoiding the causes and consequences of potential threats and risks. Consequently, the energy security strategy also considers the features of technological, environmental, resource, and social security. Even though the solution to the problem of energy security is aimed at achieving national goals, at the same time, minor problems remain out of consideration. Therefore, short-term and long-term stages of implementation should be taken into account when developing an appropriate strategy. Regarding the effectiveness of this strategy, the necessary conceptual tools and methodological directions for further generalization should be substantiated. Considering Ukraine’s Energy Strategy until 2035, "Security, Energy Efficiency, Competitiveness", appropriate types of energy strategies should be developed to increase energy efficiency, strengthen energy security standards and principles and prevent potential threats.